An Analogue of Shannon Information Theory for Detection and Stabilization via Noisy Discrete Communication Channels - Matveev, Alexey S.; Savkin, Andrey V. (SIAM journal on control and optimization, 2007)
The paper addresses both detection and stabilization problems involving communication errors and capacity constraints. Discrete-time partially observed linear systems are studied. Unlike the classic theory, the sensor signals are transmitted to the estimator/controller over a noisy digital communication link modeled as a stochastic stationary discrete memoryless channel. It is shown that for noise-free plants, the Shannon capacity of the channel constitutes the border separating the cases where stabilization and reliable detection (asymptotic state estimation) with arbitrarily large probability are and are not possible, respectively.